2023
DOI: 10.1111/aos.15730
|View full text |Cite
|
Sign up to set email alerts
|

Association between visual impairment and suicide: A systematic review and meta‐analysis

Amanda Palbo,
Marie Louise Roed Rasmussen,
Michael Stormly Hansen
et al.

Abstract: Visual impairment severely impacts the life of the patients. In this study, we systematically reviewed studies on the potential relationship between visual impairment and suicidal behaviour, and conducted meta‐analyses on the risk estimates. We searched 11 literature databases on 20 October 2022 and identified a total of 10 eligible studies with 5.8 million participants. Suicide behaviour was investigated according to three domains: suicide ideation, suicide attempt and suicide death. In the 10 eligible studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Rajeshkannan et al 64 with visual impairment. However, the restricted number of studies integrated into their analysis impeded Palbo et al 65 from achieving precise measurements of risk magnitude and constrained their potential to conduct additional analyses. Our report encompasses 31 studies identified through meticulous literature searches, thus allowing for comprehensive summary estimates regarding the association between visual impairment and risk of suicide and facilitating the execution of metaregression analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rajeshkannan et al 64 with visual impairment. However, the restricted number of studies integrated into their analysis impeded Palbo et al 65 from achieving precise measurements of risk magnitude and constrained their potential to conduct additional analyses. Our report encompasses 31 studies identified through meticulous literature searches, thus allowing for comprehensive summary estimates regarding the association between visual impairment and risk of suicide and facilitating the execution of metaregression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Rajeshkannan et al identified a correlation between suicidal ideation (OR, 1.53 [95% CI, 1.30-1.79]) or suicide attempt (OR, 4.55 [95% CI, 2.39-8.67]) and visual impairment based on 6 relevant studies. Palbo et al, having integrated 8 studies into a quantitative analysis, also posited elevated risks of suicide death (OR, 7.00 [95% CI, 2.30-21.40]), suicide attempt (OR, 2.62 [95% CI, 1.29-5.31]), and suicidal ideation (OR, 1.83 [95% CI, 1.40-2.40]) among individuals with visual impairment. However, the restricted number of studies integrated into their analysis impeded Palbo et al from achieving precise measurements of risk magnitude and constrained their potential to conduct additional analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of visual impairment goes beyond day‐to‐day activities. Older adults with loss of visual function have worse physical and cognitive functioning, and is linked with an increased risk of comorbidity (Crews et al., 2006), disability (Lam et al., 2013), and mortality (Christ et al., 2014; Palbo et al., 2023).…”
Section: Frailty In Geographic Atrophy and Visual Impairmentmentioning
confidence: 99%